RELATIONSHIPS BETWEEN AEROBIC AND ANAEROBIC CARDIOPULMONARY INDICES OF YOUNG MALE SOCCER PLAYERS WHEN PERFORMING LABORATORY FUNCTIONAL TESTS - Borislava Petrova (Scientific Publishing House. NSA Press, 2021)
Soccer is a high-intensity intermittent team sport where both the aerobic and anaerobic energy systems contribute to the physiological demands of the game. The study aims to search and determine relationships between the values of cardiopulmonary and gas exchange indices during frequently used laboratory tests - the CardioPulmonary Exercise Test (CPET) and the Wingate Anaerobic Test (WAnT), exploring the capacity of the energy systems. Forty-seven soccer players (15.06 ± 0.84 years of age) performed both tests as Oxygen uptake (VO2 ), Oxygen pulse (O2 HR), Pulmonary ventilation (VE), Volume of expired air (VTex), and Breath frequency (BF) were measured online using a breath-by-breath cardiopulmonary exercise testing system. Ergometric achievements during WAnT: PP (Peak Power) 662.4 ± 121.2 W; AP (Average Power) 494.67 ± 98.5 W; FI (Fatigue Index) 61.2 ± 28.7%. There was no correlation between WAnT PP and AP and maximum power output in CPET. WAnT VE and VTex correlate significantly with CPET VO2 max (r = .676 and r = .772, respectively). The main finding was a presence of approximately identical maximal values of cardiopulmonary parameters achieved in the very different in duration and intensity CPET and WАnT: insignificant differences between CPET versus WAnT: VO2 max (55.97 ± 2.02 versus 56.02 ± 17.3 ml.kg.min-1); VEmax (133.96 ± 21.77 versus 126.77 ± 24.77 l.min-1); VTex max (2.19 ± 0.37 l versus 2.06 ± 0.43 l); BFmax (62.20 versus 75.43.min-1). We assume that when conducting WAnT with simultaneous registration of respiration, together with the indices of athletes' power output, reliable information about the magnitude of VO2max and other cardiopulmonary parameters of players could be obtained. This will greatly facilitate the ongoing control of the exercise conditioning status of athletes.